The Research of Gray Algorithm and Information Entropy in Route Planning Optimization - Ke Zhao (Institute of Advanced Engineering and Science, 2012)
In order to solve the Unmanned Aerial Vehicle (UAV) 3-d track planning problems, according to UAV flight are subject to different threats, UAV flight track was established optimal decision-making system, and the fuel consumption, radar threats, missile threats, anti-aircraft threats and atmosphere threats are determined as the evaluation index of objective function, and optimal mathematical model of UAV flight track is constructed. Experience evaluation method is often used to Weight calculation, but there is certain subjectivity .Therefore information entropy method is adopted to determine the Weights by the set of track plans. Grey incidence analysis method is applied to deal with the gray correlation information between the various indicators and to solve the model. Finally, the optimal model is used to scheme selection for flight track planning problem with four threat radar points, five missile threat points, six artillery threat points and four climate threat points to the threat point of flight track planning scheme options. And get the flight track with the best overall performance and Minimum Comprehensive cost, the research provides a theoretical basis for further studying the three-dimensional UAV flight track optimization. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1635